EFFORTS TO IMPROVE KNOWLEDGE OF TYPE 2 DIABETES MELLITUS (DM) DIETS AT X HOSPITAL: A CASE STUDY - Chyntia Anesiaa; Lia Natalia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Type 2 diabetes mellitus (DM) is a chronic disease with an increasing prevalence and a risk of serious complications if left uncontrolled. One of the main pillars of DM management is diet control based on the 3J principle (amount, type, and schedule). However, low patient knowledge remains an obstacle to diet compliance and blood glucose control. This study aims to determine efforts to improve dietary knowledge in patients with Type 2 Diabetes Mellitus through diet education based on the 3J principle at Hospital X. Method: The study used a case study design with a descriptive approach. The research subjects were three type 2 DM patients who met the inclusion criteria, namely being able to communicate well and able to read and write. The intervention in the form of DM dietary education based on the 3J principle was carried out directly using lectures and question and answer sessions for approximately 15 minutes. Knowledge levels were measured before and after the intervention using a DM dietary knowledge questionnaire that had been tested for validity. The data were analyzed descriptively. Results: All subjects experienced an increase in knowledge scores with an average increase of 3–4 points. Two patients improved from the poor knowledge category to the good category, while one patient improved from the poor category to the adequate category. In addition, all patients experienced a decrease in fasting blood glucose (FBG) values after the intervention, indicating an improvement in glycemic control in the short term. Conclusion: Diabetes Mellitus diet education based on the 3J principle effectively improves the knowledge of type 2 DM patients and has the potential to support blood glucose control. Brief and structured education can be an applicable nursing intervention to improve patients' self-care abilities in managing chronic diseases.